Costs and benefits of urban dispersion on a local scale: presentation of an ongoing research project - Carvalho, Jorge Afonso (2009)
There is an increasing urbanization of the world population, but the city has been taking new shapes,different from traditional compact and continuous forms. In the emergent city, mobility has transformed social and spatial relations, construction is intertwined with increasingly abandoned green spaces and the urban structure is fragmented and dispersed. Such dispersion, even without many defenders among key urban theorists, is nowadays a reality, unplanned, but practised and accepted. Arguments for and against dispersion have long been confronted, remaining unchanged: for some, it means contact with nature, space and intimacy; for others, it is a simulacrum of nature, isolation and anonymity. Such subjective arguments are important in the identification of different concepts of quality of life. But there are other arguments, objective ones: land consumption, public infrastructure costs, mobility costs and housing prices. The Research Project “Costs and Benefits of Urban Dispersion on a local scale”, from which this communication derives, seeks opinion, as precise as possible, on these issues. To do so, it will consider costs and benefits. Studies seeking to quantify costs, relating mainly to the USA, analyse dispersion, the majority of times, on a regional scale. In this Project, we intend to compare costs between different “Base Land Units” of the extended city – a concept similar to that of the neighbourhood unit or of the neighbourhood itself. Our main goal is, then, to analyse and, if possible, to confront costs and benefits of different land use types. By benefits we understand quality of life, a concept that changes from opinion group to opinion group. We intend to transform this concept into an algorithm which integrates this variability, based on the current literature, similar previous studies and on the answers to a questionnaire applied to the inhabitants of Aveiro-Ílhavo and Évora (our case studies).Regarding costs, we will look at local public infrastructure (including networks, all public space and public equipments) and mobility (integrated costs per km and per user for each transport mode). Quantification of costs relating to land consumption and other environmental externalities (nature and landscape based) has to be left for a later research opportunity. Our conclusions, supported by public questionnaires, will be expressed quantitatively: an utility function to represent opinions on quality of life; an integrated cost for local infrastructure + mobility; and a methodology to relate the two functions for a variety of scenarios. This will result in the formulation of a comparative opinion, expressed in cost-benefit terms, between the various typologies of dispersed occupation and, also, between these and those of continuous occupation. To formulate an operative proposal regarding urban dispersion, it is important to understand how the market works (in terms of its agents, procedures and prices) for current dispersed occupation dynamics. This paper will go through the work undertaken so far, describing concepts and methods and presenting preliminary results when possible. It will not only focus on the Project’s general methodology, but also on methodologies specific to each Task, whenever it is thought appropriate.